Fine mapping of a region of chromosome 11q23.3 reveals independent locus associated with risk of glioma. - Hongyan Chen (Public Library of Science (PLoS), 2012)
Background A single nucleotide polymorphism (SNP) at locus 11q23.3 (rs498872) in the near 5'-UTR of the PHLDB1 gene was recently implicated as a risk factor for gliomas in a genome-wide association study, and this involvement was confirmed in three additional studies. Methodology/principal findings To identify possible causal variants in the region, the authors genotyped 15 tagging SNPs in the 200 kb genomic region at 11q23.3 locus in a Chinese Han population-based case-control study with 983 cases and 1024 controls. We found evidence for an association between two independent loci (both the PHLDB1 and the ACRN1 genes) and a predisposition for gliomas. Among the multiple significant SNPs in the PHLDB1 gene region, the rs17749 SNP was the most significant [P = 1.31×10⁻⁶ in a recessive genetic model]. Additionally, two novel SNPs (rs2236661 and rs494560) that were independent of rs17749 were significantly associated with glioma risk in a recessive genetic model [P = 1.31×10⁻⁵ and P = 3.32×10⁻⁵, respectively]. The second novel locus was within the ARCN1 gene, and it was associated with a significantly reduced risk for glioma. Conclusions/significance Our data strongly support PHLDB1 as a susceptibility gene for glioma, also shedding light on a new potentially candidate gene, ARCN1.